Syntax and Lexicon in Agricultural Proverbs: A Comparative Study of English and Indonesian - Giyatmi Giyatmi; Sihindun Arumi; Ratih Wijayava (CV. Rustam, 2025)
The study aims to compare Indonesian and English proverbs with agricultural themes in terms of syntactic structures and lexical choices. The study employs a descriptive qualitative method with a comparative approach. The data consist of 20 agricultural English proverbs found on a website, meanwhile their Indonesian counterparts were obtained from various online sources. Although the dataset is limited in size, the selection process was carefully designed to reduce imbalance and potential bias. The selection and pairing of these proverbs were carried out by applying semantic justification to ensure that both languages reflect comparable meanings. The data were collected through documentation, organized into tables, and analyzed syntactically and lexically. The analysis reveals that both sets of proverbs employ simple, compound, and complex sentences, with complex sentences being the most dominant. The phenomenon indicates that agricultural proverbs in both languages tend to consist of layered wisdom and conditional reasoning, reflecting the complexity of human interaction with nature. Compound sentences, however, are the least frequently found. It suggests that proverbs seldom rely on coordination but rather emphasize subordination and cause-and-effect relations. Lexically, both languages share terms related to seasons, weather, agricultural tools, activities, animals, and plants; however, the specific choices differ due to the cultural and ecological contexts. English proverbs often include words such as